Clinical Manifestations, Pathogenesis, Diagnosis and Treatment of Peripheral Neuropathies in Connective Tissue Diseases: More Diverse and Frequent in Different Subtypes than Expected - Lei Jin; Yu Liu (Diagnostics, 2021)
Purpose of review: To discuss and summarize recent findings in peripheral neuropathy (PN) related to connective tissue diseases (CTD) including its prevalence, clinical manifestations, pathogenesis, diagnosis and treatment. Recent findings: Although PN is a common complication in CTD and has been well studied, recent research has shown that PN is more diverse and frequent in different subtypes of CTD than was expected. The incidence of PN in Sjögren’s syndrome and rheumatoid arthritis (RA) varies according to different disease subtypes, and the pathogenesis of neuropathic pain in different subtypes of eosinophilic granulomatosis with polyangiitis (EGPA) may also differ. Neurogenic inflammation, autoantibody-mediated changes, ischemia of the vascular wall and metabolic mechanisms have been shown to contribute to the pathogenesis of PN in CTD. Moreover, allergic inflammation has been recently identified as a possible new mechanism producing peripheral neuropathic pain associated with MPO-ANCA negative EGPA patients. Glucocorticoids are routinely used to relieve pain caused by PN. However, these steroids may cause hyperalgesia, exacerbate neuropathic pain, and activate the early phase of pain induction and produce hyperalgesia. Recently, neuroactive steroids, such as progesterone, tetrahydroprogesterone and testosterone, have been shown to exert protective effects for several PN symptoms, and in particular neuropathic pain. Neuroactive steroids will be an interesting topic for future research into PN in CTD. Summary: It is essential for the diagnosis and treatment of PN in CTD to be updated. Timely diagnosis, appropriate treatments, and multidisciplinary care are essential to minimize morbidity and decrease the risk of permanent neurologic deficits. Further studies are needed to guide diagnosis and treatment.